Sphingosine-1-Phosphate Transporters as Targets for Cancer Therapy. (15th July 2014) - Nagahashi, Masayuki; Takabe, Kazuaki; Terracina, Krista P.; Soma, Daiki; Hirose, Yuki; Kobayashi, Takashi; Matsuda, Yasunobu; Wakai, Toshifumi
Abstract : Sphingosine-1-phosphate (S1P) is a pleiotropic lipid mediator that regulates cell survival, migration, the recruitment of immune cells, angiogenesis, and lymphangiogenesis, all of which are involved in cancer progression. S1P is generated inside cancer cells by sphingosine kinases then exported outside of the cell into the tumor microenvironment where it binds to any of five G protein coupled receptors and proceeds to regulate a variety of functions. We have recently reported on the mechanisms underlying the "inside-out" signaling of S1P, its export through the plasma membrane, and its interaction with cell surface receptors. Membrane lipids, including S1P, do not spontaneously exchange through lipid bilayers since the polar head groups do not readily go through the hydrophobic interior of the plasma membrane. Instead, specific transporter proteins exist on the membrane to exchange these lipids. This review summarizes what is known regarding S1P transport through the cell membrane via ATP-binding cassette transporters and the spinster 2 transporter and discusses the roles for these transporters in cancer and in the tumor microenvironment. Based on our research and the emerging understanding of the role of S1P signaling in cancer and in the tumor microenvironment, S1P transporters and S1P signaling hold promise as new therapeutic targets for cancer drug development.